An isotopic generation: four decades of stable isotope analysis in African archaeology. Issue 1 (2nd January 2016) - Loftus, Emma; Roberts, Patrick; Lee-Thorp, Julia A.
ABSTRACT: The application of stable isotope analysis in African archaeology has a long and distinguished pedigree. Many new developments were inspired by questions in the archaeology of the continent, helped considerably by the availability of African landscapes as natural laboratories for providing the essential underpinning of isotope ecology systematics. Stable isotopes are now regularly built into multi-disciplinary archaeological projects spanning the very long temporal and geographical span of human history on the African continent. On the fiftieth anniversary of Azania: Archaeological Research in Africa we evaluate these endeavours — the achievements, problems, constraints and potential of stable isotopic research in African archaeology. We begin with a discussion of the continent's role in developing understandings of stable carbon, nitrogen, oxygen and strontium isotope systematics, as used to interpret change in the archaeological record. We discuss the application of these principles within several areas of archaeological research, drawing on case studies from among late Pleistocene/Holocene hunter-gatherers, early food producers, complex societies of the African Iron Age and the individual life histories of the African slave trade. There is clearly much potential for further application in African archaeology.